The school of hard knocks: systemic violence and the motivation to harm in boys’ youth academy football - Gibbs, Nick; Briggs, Daniel (Frontiers in Sociology, 2025)
The ‘beautiful game’ of football may seem to be a curious artifact of study for this scholarly collection on violence. However, this article will highlight the need to explore the boys’ English youth academy (YA) football industry as a manifestation of systemic violence and, ultimately, a reflection of the pseudo-pacified neoliberal economy. Embedding our theoretical analysis within emerging literature on harm and violence, this paper will illuminate the dark underbelly of boys’ elite-level youth football in England, examining the culture and relationships between academy players, YAs as breeding grounds for neoliberal subjectivities, the common practice of granting false hope to a ‘supporting cast’ of boys, and the underpinning inequalities in the elite academy industry. Drawing on data gleaned from thirty-five semi-structured interviews with current professional football practitioners and officials, as well as two former YA players, the work will provide a multifaceted analysis of the baked-in violence of the boys’ youth academy system. We will argue that we ought to challenge the assumption of harmlessness that currently cloaks the systemic violence of the boys’ elite game and move beyond interventionitis, in favor of wholesale change.